Application of mind maps as a learning resource for university students - Garay-Argandoña, Rafael; Hernández, Ronald M.; Esguiagola-Aranda, Estrella; Rodríguez-Vargas, Martha Cecilia; Salvatierra Melgar, Angel (Opción, 2020)
The research aims to know the effectiveness of the application of mind maps as a didactic resource in the learning of university students. The study was applicative, with a quasi-experimental design, we worked with a sample of 78 students from a university in Lima, Peru. As a result, it can be shown that both the control and experimental groups do not present significant differences in the pretest. In conclusion, teaching is not only about providing information, but also about helping to learn, and to do so the teacher must have a good knowledge of his/her students.